Analysis of differences in early detection of chronic kidney disease with urine creatinine, proteins and individual health status based on behavioural, stress and genetic factors in Kendari City, Indonesia - Tasnim, Tasnim; Sugireng, Sugireng; Imran, Imran; Akib, Nur Illiyyin (YCAB Publisher, 2024)
Background:Early detection of chronic kidney disease needs to be developed because the prevalence of chronic kidney disease continues to increase in Kendari City, Indonesia. Objective:The study aimed to analyse of differences in early detection of chronic kidney disease with urine proteins, creatinine, and individual health status based on behaviours, psychological-stress environment and genetic factors in Kendari City, Indonesia. Methods:This research used quantitative method with a cross sectional study approach. This study was conducted in Kendari City, Southeast Sulawesi, Indonesia, which recruited 136 subjects aged between 24-70 years. The participants were interviewed and tested urine. The dependent variables are protein-urine, creatinine, and health status. The independent variables are behaviours, psychological environment-stress and genetics. Data analysis used multinomial logistic regression statistical tests. Results: This study suggests that there are differences between tests for urine protein levels, creatinine and individual health status for early detection of chronic kidney disease which is associated with behaviours, psychological-stress environment and genetic factors in Kendari City. Protein-urine can be used early detection of chronic kidney disease which is related to daily water consumption (p=0.001, OR=1.56), calory intake (p=0.036, OR=2.13) and psychological stress environment (p=0.017, OR=0.11). However, urine creatine test cannot be use for early detection of chronic kidney disease. Meanwhile, individual’s health status can be used to early detection of chronic kidney disease with relating to daily water consumption behaviour of less than 1000 ml a day (p<0.0001, OR=1.56), physical activity (p<0.05, OR=5.7), medication adherence (P<0.01, OR=0.4), and psychological stress environment (p<0.0001, OR=8.6). Conclusion: Early detection of chronic kidney disease may be more effective by observing health status directly, or by urine protein testing, compared to urine creatinine testing. Keywords:Chronic kidney disease, behaviour, genetic, stress, proteins.